West African Economic and Monetary Union (WAEMU) : Staff Report on Common Policies for Member Countries. (IMF Staff Country Reports; Country Report ;, 2013)
Military coups that occurred in Guinea-Bissau and Mali caused economic disruption in the WAEMU countries. Regional policies have been in line with the recommendations, and growth is expected to remain robust, risks are on the downside, and the macroeconomic policy is appropriate. Preserving debt sustainability and stability of the Union in the medium term requires better coordination of fiscal policies. Development of the financial system, and strengthening of the regulatory and supervisory framework is necessary to address existing and new risks.